2020
DOI: 10.3389/fcell.2019.00395
|View full text |Cite
|
Sign up to set email alerts
|

‘Omics Approaches to Explore the Breast Cancer Landscape

Abstract: Breast cancer incidence is increasing worldwide with more than 600,000 deaths reported in 2018 alone. In current practice treatment options for breast cancer patients consists of surgery, chemotherapy, radiotherapy or targeting of classical markers of breast cancer subtype: estrogen receptor (ER) and HER2. However, these treatments fail to prevent recurrence and metastasis. Improved understanding of breast cancer and metastasis biology will help uncover novel biomarkers and therapeutic opportunities to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 143 publications
(164 reference statements)
0
40
0
Order By: Relevance
“…In the last decade, OMICS technologies have contributed to our understanding of the pathogenesis of cancer [27][28][29][30] leading to the development of precision oncology 31,32 , where selection of the patients for treatment is fundamental for better therapy outcome 33 . Therefore, identification of novel biomarkers for guiding treatment selection is a key requirement 14,[34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, OMICS technologies have contributed to our understanding of the pathogenesis of cancer [27][28][29][30] leading to the development of precision oncology 31,32 , where selection of the patients for treatment is fundamental for better therapy outcome 33 . Therefore, identification of novel biomarkers for guiding treatment selection is a key requirement 14,[34][35][36] .…”
Section: Discussionmentioning
confidence: 99%
“…Mass spectrometry (MS)-based proteomics has led to the possibility of characterizing and quantifying the protein profile of biological specimens, as well as the possibility to discover their complex interactions involved in various specific pathologies. For example, various proteomic approaches combined with genomic analysis have been used in cancer research for obtaining more information about the molecular basis of tumor genesis and the development of more effective anticancer therapies [17][18][19].…”
Section: Proteomicsmentioning
confidence: 99%
“…This type of quantitation works well enough for pilot and preliminary studies, but findings should be confirmed later using a more precise, reliable method. Labeling methods for quantification are also abundant, including methods such as isotope-coded affinity tag (ICAT), stable isotope labeling by amino acids in cell culture (SILAC), 15 N/ 14 N metabolic labeling, 18 O/ 16 O enzymatic labeling, isotope coded protein labeling (ICPL), tandem mass tags (TMT), and isobaric tags for relative and absolute quantification (iTRAQ) [173]. The absolute quantification (AQUA) method allows for the precise determination of protein expression and even post-translational modification levels by mimicking the exact peptide of interest, with the exception of stable isotope enrichment [174].…”
Section: The Goodmentioning
confidence: 99%
“…However, a study from the Mayo Clinic showed that only a small number of patients with actionable genetic mutations could benefit from genotype‐directed therapy [17]. Recently, the integration of PDX models to multi‐omics technologies, such as genomics, transcriptomics, proteomics, and metabolomics, has contributed abundantly to the understanding of cancer biology and the discovery of novel targets or biomarkers [18]. It is reasonable to assume that the combination of PDX 2.0 models with omics analysis could be a robust method to indicate individual therapeutic regimens.…”
Section: Main Textmentioning
confidence: 99%